Pendampingan Masyarakat dalam Pemenuhan Rumah Sehat di Kampung Klablim Kelurahan Aimas Kabupaten Sorong - Jenni Lilis S Siagian; Hansen Maikel Su; Maylar Gurning (PT.Mantaya Idea Batara, 2022)
The increase in the degree of public health is marked by the population living with proactive behavior maintain and improve, present the risk of disease, protect themselves from the threat of disease and actively participate in the public health movement. There are 168 people in Klablim Village Aimas Sorong Regency, the problem is that there are still houses that do not meet the standarts. Level of community knowledge in Klablim Village Sorong Regency is quite good but level of community behavioris not good. The purpose of this community service is to assist the community in fulfilling healthy homes, providing knowledge about healthy so homes so that people know the risks that arise from unhealthy homes and are able to fulfil healthy homes. Assistance community in fulfill healthy homes is carried out for 30 days, through outreach activities and assiting the community in efforts to fulfil healthy homes. The assistance of the people of Village Klablim in fulfilling healthy home has beeb carried out, and the community has been aware of the problems of healthy homes and is able to assest the risk that may be face. It is hoped that the community will be able to meet healthy homes in accordance with applicable regulations, inan effort to improve health status.